Stylistic gender differences in the literary representation of detective talk - Ortells Montón, Elena; Posteguillo Gómez, Santiago (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2002)
Although substantial work has already been done on the variation between men and women in real speech, not so much has been carried out on the representation of speech in literature. The ample presence of dialogic interactions in the detective novel turns the genre into an extremely productive field of research in relation to represented conversation. In this paper, a corpus consisting of 79 one-to-one dialogues from eight different novels written by four well-known and best-selling authors is analysed according to six research questions. We believe it is the context, the pragmatic situation which makes women either maintain their speech style and represent it in fiction as it is or change it because they want to ascribe themselves and their written representations to a specific genre and a particular profession respectively.